Education and Practice of Pesantren (Al-Ma’had al-Islāmī) in Islamic Economics Until Business the Perspective of Anthropologist Clifford Geertz - Khaer, Abu; Rosyid, Abdul; Khalimi, Khalimi; Istifhama, Lia (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
At present, there is limited understanding of Pesantren (al-Ma’had al-Islāmi) as educational institutions that not only provide religious instruction but also incorporate economic and business education grounded in Islamic principles. The distinctiveness of Pesantren, particularly regarding their Islamic economic and business frameworks and practices, remains underexplored, leading to hesitance in articulating the methodologies employed, especially from an anthropological viewpoint. This journal article examines the anthropology of Islamic economic and business education and practices within Pesantren through the lens of Clifford Geertz. This paper aims to address existing scholarly uncertainties. The author employs a qualitative research methodology utilizing a naturalistic-phenomenological approach. The primary data source for this study is Geertz's anthropological analysis of Religion and Agricultural Involution in Java, Indonesia. The findings indicate that, from Geertz's anthropological perspective, Pesantren, referred to as santri circles, exhibit a close relationship with economic and business behavioral paradigms. This conclusion also addresses the gaps in the fundamental components of Pesantren anthropology, aligning with Martin van Bruinessen's assertion that these components include kyai, santri, pondok, yellow book studies, and educational practices within Pesantren. Furthermore, the elements of economic and business activities are integral to the civilization of Pesantren